Fiscal Transparency and Fiscal Policy Outcomes in OECD Countries - James E. Alt; David Dreyer Lassen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2003)
It is widely believed and often argued that fiscal, or budgetary, transparency has large, positive effects on fiscal performance. However, the evidence linking transparency and fiscal policy outcomes is far from compelling. We present a career-concerns model with political parties to analyze the effects of fiscal transparency on public debt accumulation. To test the predictions of the model, we construct a replicable index of fiscal transparency. Simultaneous estimates of debt and transparency on 19-country OECD data strongly confirm that a higher degree of fiscal transparency is associated with lower public debt and deficits.
Keywords: 330; Öffentliche Finanzen; Finanzkontrolle; OECD-Staaten; Fiskalische Transparenz